PREVALENCE AND MOLECULAR CHARACTERIZATION OF TOXOPLASMA GONDII IN RETAIL RED MEAT SAMPLES ACROSS ERBIL GOVERNORATE, KURDISTAN REGION, IRAQ: IMPLICATIONS FOR FOOD SAFETY AND PUBLIC HEALTH - Ahmed , Kareem Hussein; Ali, Layla Hassan (Global Journal of Medical and Health Science, 2023)
Toxoplasma gondii, a widespread protozoan parasite, poses a significant public health challenge globally. This study aimed to detect anti-T. gondii antibodies in human blood samples using immunological tests and investigate potential risk factors. A total of 520 blood samples were collected from individuals aged 10 to 71 years and tested using latex, lateral flow assay, and Enzyme-linked immunosorbent assay (ELISA). The results revealed varying seropositivity rates, with 23.3%, 25.4%, 20.2%, and 9.8% of samples testing positive for latex, lateral flow assay, ELISA IgG, and ELISA IgM, respectively. Notably, the elderly age group exhibited a higher prevalence of T. gondii antibodies, with seropositive rates of 26.1%, 27.5%, and 23.2% for latex, lateral flow assay, and ELISA IgG, respectively. The study identified two major risk factors associated with T. gondii infection: contact with raw meats and consumption of raw vegetables. These findings suggest that incorporating latex and lateral flow assays into routine screening can be a cost-effective strategy for T. gondii diagnosis. To reduce the risk of infection, consumers are strongly recommended to thoroughly cook animal-origin food and practice meticulous washing of vegetables and fruit before consumption. These measures play a crucial role in minimizing the transmission of T. gondii and protecting public health